Do Written Disclosures of Serious Events Increase Risk of Malpractice Claims? One Health Care System's Experience. Issue 2 (June 2018) - Painter, Lisa M.; Kidwell, Kelley M.; Kidwell, Richard P.; Janov, Cheryl; Voinchet, Robert G.; Simmons, Richard L.; Wu, Albert W.
Abstract : Objective: This study aimed to determine whether Pennsylvania ACT 13 of 2002 (Mcare) requiring the written and verbal disclosure of "serious events" was accompanied by increased malpractice claims or compensation costs in a large U.S. health system. Main Outcomes and Measures: The primary outcome was the rate of malpractice claims. The secondary outcome was the amount paid for compensation of malpractice claims. The analyses tested the relationship between the rate of serious event disclosures and the outcome variables, adjusted for the year of the event, category of claim, and the degree of "harm" related to the event. Results: There were 15, 028 serious event disclosures and 1302 total malpractice claims among 1, 587, 842 patients admitted to UPMC hospitals from May 17, 2002, to June 30, 2011. As the number of serious event disclosures increased, the number of malpractice claims per 1000 admissions remained between 0.62 and 1.03. Based on a matched analysis of claims that were disclosed and those that were not (195 pairs), disclosure status was significantly associated with increased claim payout (disclosures had 2.71 times the payout; 95% confidence interval, 1.56–4.72). Claims with higher harm levels H and I were independently associated with higher payouts than claims with lower harm levels A to D (11.15 times the payout; 95% confidence interval, 2.30–54.07). Conclusions and Relevance: Implementation of a mandated serious event disclosure law in Pennsylvania was not associated with an overall increase in malpractice claims filed. Among events of similar degree of harm, disclosed events had higher compensation paid compared with those that had not been disclosed. Abstract : Supplemental digital content is available in the text.